Lead time on confirmatory test after abnormal Pap test in the COVID-19 era. Issue 39 (1st October 2021) - Kim, Miseon; Lee, Nara; Won, Seyeon; Kim, Ju-Hyun; Kim, Mi Kyoung; Kim, Mi-La; Jung, Yong Wook; Yun, Bo Seong; Seong, Seok Ju
Abstract : Abstract: During the COVID-19 pandemic, there are concerns about medical delay, including confirmatory tests after screening for various cancers. We evaluated the lead time to a confirmatory test after an abnormal screening Papanicolaou (Pap) test in women before the COVID-19 period and during the COVID-19 period. The medical records of 1144 women who underwent colposcopy at a single institution located in Seoul after abnormal Pap results from January 2019 to December 2020 were reviewed. The lead time to colposcopy from the Pap test between 2019 and 2020 was compared; the adverse factors for a long lead time to colposcopy were also evaluated. Age, residence, institution, and the Pap results did not differ between women who underwent colposcopy in 2019 (n = 621) and 2020 (n = 523). The time to colposcopy from the Pap test was also not different. A higher number of women were diagnosed with high-grade dysplasia in 2020 and underwent excision procedures; however, the difference was not statistically significant. Instead, patients' residence, institution of the Pap test, and results of the Pap test were associated with a long lead time to colposcopy of >6 weeks. The lead time to colposcopy from the abnormal Pap test was not delayed in the COVID-19 era compared to before. However, regional factors could affect a long lead time.